Sensors and actuators : control systems instrumentation - De Silva, Clarence W. (Boca Raton, FL : CRC Press, 2007)
Control systems are found in a wide variety of areas, including chemical processing, aerospace, manufacturing, and automotive engineering. Beyond the controller, sensors and actuators are the most important components of the control system, and students, regardless of their chosen engineering field, need to understand the fundamentals of how these components work, how to properly select them, and how to integrate them into an overall system. In Sensors and Actuators: Control System Instrumentation, bestselling author and expert Clarence de Silva outlines the fundamentals, analytical concepts, modeling and design issues, technical details, and practical applications of these devices. This text begins with a general introduction to control and various types of control systems, followed by component interconnection, signal conditioning, and performance specification and analysis. The author then systematically describes important types, characteristics, and operating principles of analog sensors, digital transducers, stepper motors, continuous-drive actuators, and mechanical transmission components, progressing from basic to more advanced concepts. Throughout the book, convenient snapshot windows summarize important and advanced theory and concepts, accompanied by numerous examples, exercises, case studies, and end-of-chapter problems.
Optical Sensors and Lasers -- Ultrasonic Sensors -- Thermofluid Sensors -- Other Types of Sensors Problems -- DIGITAL TRANSDUCERS -- Advantages of Digital Transducers -- Shaft Encoders -- Incremental Optical Encoders -- Absolute Optical Encoders -- Encoder Error -- Miscellaneous Digital Transducers Problems -- STEPPER MOTORS -- Principle of Operation -- Stepper Motor Classification -- Driver and Controller -- Torque Motion Characteristics -- Damping of Stepper Motors -- Stepping Motor Models -- Control of Stepper Motors -- Stepper Motor Selection and Applications -- Problems -- CONTINUOUS-DRIVE ACTUATORS -- DC Motors -- DC Motor Equations -- Control of DC Motors -- Motor Driver -- DC Motor Selection -- Induction Motors -- Induction Motor Control -- Synchronous Motors -- Linear Actuators -- Hydraulic Actuators -- Hydraulic Control Systems -- Fluidics Problems -- MECHANICAL TRANSMISSION COMPONENTS -- Mechanical Components -- Transmission Components -- Lead Screw and Nut -- Harmonic Drives -- Continuously Variable Transmission Problems -- BIBLIOGRAPHY AND FURTHER READING -- ANSWERS TO NUMERICAL PROBLEMS -- INDEX.
Includes bibliographical references (p. 647-651) and index.
1
Keywords: Automatic control; Detectors; Actuators